AGAMA DALAM KERANGKA PIKIR ATEISME JEAN-PAUL SARTRE - Anas Ahmad (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2009)
Abstract. Today, atheism is one of the most interesting topics to discuss both in academic and nonacademic forums, especially Jean-Paul Sartre’s atheism-existentialism. In this research, the writer is talking about religion in accordance with  the atheism of Jean-Paul Sartre –atheisme- existentialism. In this paradigm,  atheism  including (1) child atheism, (2) young atheism, dan (3) old atheism. Key words: religion, atheism, existentialism